Donald Trump’s new administration and continuity in U.S. strategic planning - O. M. Aleksandriya; A. G. Savelyev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2025)
Every new U.S. administration adopts and publishes a series of key documents outlining the official stance on the most pressing domestic and foreign policy issues. Among the latter issues of war and peace, the assessment of threats and challenges to international security and the role of military force and nuclear weapons in ensuring it occupy not the last place. At the same time, each succeeding administration inevitably adjusts its predecessors’ views on these matters, especially if they belong to a rival political party. In this context, the return of Donald Trump to the U.S. presidency in 2025 creates a special intrigue. To under- stand both the contours of the updated U.S. strategy in the field of international security and its correlation with the approaches of previous administrations, the authors examine the key American political and military planning documents across the following issue areas: 1) overall assessments of the international situation; 2) perceived major security threats and challenges; 3) likely adversaries of the United States; 4) the role of nuclear weapons in the U.S. security policy; 5) views on strategic stability and strategic deterrence; 6) requirements for the U.S. nuclear forces; 7) priorities within nuclear forces modernization programs; and 8) positions on nuclear arms control. The authors conclude that the new Trump administration will undoubtedly introduce certain modifications to the strategic planning documents adopted under Joe Biden, particularly in terms of strengthening the role of nuclear weapons in security policy and advancing missile defense systems. The strategy’s primary focus will likely shift toward China, while Russia-related issues may be deemed less pressing and more manageable in terms of U.S. interests. Meanwhile, nuclear arms control will recede, although efforts to engage China in these activities may continue. Mapped out modernization programs for U.S. strategic nuclear forces will remain intact but could be supplemented by expanded missile defense initiatives. In general, the U.S. security policy is expected to take a more assertive stance, demanding swift and effective resolution of all existing and potential challenges in this domain.